IMPLEMENTASI PRINSIP NO FIRST USE PADA KEBIJAKAN SENJATA NUKLIR TIONGKOK DI ERA PEMERINTAHAN XI JINPING 2017 - 2019 - Rahmadini Agung Ayu Utami, (2022)
This study aims to identify how the implementation of nuclear weapons policy during the leadership of Xi Jinping. The policy is based on the principle of No First Use and periodization for 2017 - 2019. The analysis uses deterrence theory, military security concepts, and security dilemma concepts. The method used in this research is descriptive qualitative with the support of primary and secondary data sources. Data collection techniques used in this research are literature study techniques and internet-based data collection techniques (internet-based research). The final result of this research is that China has been consistent in implementing this principle since the beginning of nuclear weapons development until the current Xi Jinping administration. It is evident from China which has never used its nuclear weapons to attack other countries or threaten non-nuclear countries. This is inseparable from the purpose of China's nuclear weapons which function as a means of defense or deterrence from the real nuclear attack on Chinese territory. The increase in nuclear capability during Xi Jinping's time was an effort to ease the way to achieve the ideals of the Chinese Dream. The implementation of the principle of No First Use during the leadership of Xi Jinping 2017 - 2019 is adjusted to the mission of the Chinese Dream slogan. The principle of No First Use continues to be applied consistently to China's 2017 - 2019 nuclear weapons policy, while the mission to strengthen China's military to become a great power continues.